De gevel – een intermediair element tussen buiten en binnen: Over het tonen en vertonen van het twintigste-eeuwse woongebouw in Nederland - Jürgenhake, Birgit (A+BE | Architecture and the Built Environment, 2016)
This study is based on the fact that all people have a basic need for protection from other people (and animals) as well as from the elements (the exterior climate). People need a space in which they can withdraw from the rest of the world. The two states, inside and outside, public and private, contact with, or isolation from, the outside world, are relevant in fulfilling this basic need. People also want their home to have a certain appearance or status which they can identify with and which they can present to the outside world. This can also often be derived from the façade. The façade which is on a side which can be seen by the general public can be seen by the most people. Protection and appearance/status are two important characteristics of the façade. The term social filtering is used in this study to mean protection and face or mask to mean appearance/status. The means which can be used for protection embrace a broad spectrum, of which a fence, the doorstep (threshold), the door and shutters are just some initial examples. The means which can be used to lend status to a house are just as diverse. It is impossible to make a strict distinction between the means of social filtering and those of the face or mask and they often fulfil both functions. The façade as social filter and as face or mask of the residential building is the starting point of this study. Both the roles, as social filter and face of the home, have undergone great change as a consequence of the accommodation of several homes in the one building. The history of homes in the Netherlands shows that the individual house has only been one of many dwelling possibilities since the nineteenth century ; the ‘stacking’ of homes on top of each other in larger buildings, described as residential building, became a necessity in the cities. This is why this study is focussed on the residential building and its façade in the city in the Netherlands. Two questions formed the starting point for this study: 1. How can information about the need for contact or isolation, and the need for status, be read from the exterior of a house? 2. What happens to the face and the social filter of a building when we no longer look at it as a house for just one social unit but as a residential building which accommodates several homes? The two questions resulted in an investigation into the aspects by which the social filter and the face of a façade can be read. Residential buildings designed as such to meet the demand in cities began to appear more often in the second half of the nineteenth century. Initially, they were cheap and hardly innovative. By the start of the twentieth century, the entrance to homes in the residential building, an important element of the social filter, had become a subject of study for architects and various solutions were developed. The appearance of the residential building showed, on the one hand, pragmatic approaches, but on the other, architects tried to develop a face or mask for this relatively new type of building. Throughout the twentieth century, the period covered by this study, the residential building and its façade have undergone great change. This change reflects the cultural, social, technical and economic factors which have had an effect on the design of the residential building and the significance of the façade with its social filter and its face or mask. Today, the façade of the residential building has reached a freedom which reflects the possibilities, the architect’s creative expression and the client’s commercial needs. The façade hardly contributes to the communication between life outside and the resident and his or her home inside. Social filtering, which often takes place in a dynamic way between the exterior and the interior, is still important, but now takes place to a large degree behind the façade. The face shown is neutral, if not anonymous, and hides the number of homes behind the screen. In order to follow the changes in the residential building and its façade through the twentieth century and to understand with what means architects have developed the façade in particular, the research question has been formulated as: What factors and architectonic means have been decisive in the Netherlands in the twentieth century for the façade of the residential building as an intermediary element (as face/mask and social filter) between the exterior and the interior? The aim of this study is to learn more about the factors which lead to the decisions about the design of a façade and to understand the architectonic means which are applied to make a façade readable. This study also has the aim of providing an analytical approach to looking at a façade and making a contribution to the design of buildings and a broader study of the relationship between buildings and their façades. The study is organised in a theoretical framework and the analysis of ten projects. The theoretical framework in respect of façade, face and mask (chapter 4), a historical context of residential construction (chapter 5), a context of the development of public, exterior living (chapter 6), and private, interior living (chapter 7) are included in the theoretical framework. The analysis of the ten projects is presented in chapter 8. The framework and the analysis form one whole. The analysis of the case studies demanded a method which would illustrate the façade as social filter and face or mask. In order to make the role of social filter more comprehensible, the transition from the public space in front of the main entrance to the entrance to the home has been illustrated by means of two isometric drawings. The public space of the steps from the doorstep or pavement to the private home is also documented in a diagram, and the architectonic resources which make up this transition are recorded with photos. For the analysis of the façade as a face, the parts of the human face which are easily included visually are used metaphorically. The eyes are openings, the mouth is an entrance or door, the nose is a vertical feature, the head shape of the face is the most easily read form of the building and the profile supports the information because it shows depth. Visually striking aspects of the face which protrude, recede, frame or divide can be translated in the façade as, for example, bay windows, balconies, beams, framing lintels or windowsills. Visually distinguishing lines of profiles can be seen in the form of balconies or, for instance, a switch in material. In order to use the metaphor of the human face as the foundation for an analysis in architecture, an analytical framework has been assembled. The Gestalt laws, applied to buildings by Niels Prak, demonstrate how we visually perceive the built environment. The head shape and horizontal and vertical parts and sections are perceived faster than free forms or a complex picture with a lot of different information. These laws justify the choice of the subjects for analysis which have been drawn in a reduced form. The subjects for analysis for the façade as face are: the head shape, the profile, the openings for light and for the entrance (door), visible constructional elements in the façade (horizontal and vertical), decorative parts, protruding and receding parts, material and colour. In the analysis, the sociocultural background of the project will be described, summarised as building assignment, and all the architectonic aspects will be shown which make up the social filter and appearance, summarised as building form. Façade definitions (chapter 4) The term façade means the vertical exterior of the building, just as the face practically vertical is. The roof is governed by its own principles and is not always a part of the façade unless it can be seen. The horizontal roof, like the crown of a head, cannot easily be seen. The term façade carries several meanings. The façade is something that is presented to its surroundings and that is why it is often associated with the face. The term façade (Latin facies = face) makes the connection with the metaphor of the face clear: the façade of the building is meant to be the presentable side which is shown to the public. The human face communicates non-verbally by means of expression. The façade does not have this movement and can only be called a face metaphorically. The façade can still show what happens behind it to a degree, however, what the building is for, for example. The façade can also exhibit an idea or represent an illusion; the façade is then a mask. The term garment is used for both the protective and aesthetic role of the façade. A garment keeps you warm and protects, but it can also be decorative and the status of the person wearing it can be clear if the code included in the decoration is understood. The façade therefore also fulfils this role as the conveyor of information. The degree to which the façade has a filter role is determined by the degree to which it allows things to pass though it: light, air and temperature but also people and animals. This ability to allow things to pass through it is dynamically regulated depending on the means used. Depending on the building’s spatial configuration, there may also be a front façade, rear façade or side façade. The historic context of the residential building (chapter 5) The urban house changed almost imperceptibly until the nineteenth century into a building which accommodated several homes. The construction of the residential building designed as such intensified in the second half of the century, however, when the increasing demand for housing meant that it was necessary to provide more options. The ‘stacking’ of homes in such a building meant another means of entering the building. The immediate entrance to the home increasingly withdrew from the street and communal entrances and stairwells appeared. The most important change from the individual house to the shared building was the entrance. Architects often lent expression the communal entrance, perhaps to help the resident and visitor become more familiar with its new communal aspect. Various changes to the residential building and its façade can be seen throughout the twentieth century. While architects like Hendrik P. Berlage and his followers in the first two decades enriched the façade with details and news ideas for communal entrances arose, functionalists like Willem van Tijen designed residential buildings in the thirties and during the post-war reconstruction which showed what their function was without any embellishment. Architects reacted to social, economic and technical factors. Where the first residential buildings consisted of six to eight homes per staircase per floor, the introduction of galleries and then, in the fifties, the lift, meant that many more homes could be accommodated. This was particularly the case in the sixties after the first wave of post-war reconstruction. The residential buildings were so big that it was barely possible to see the whole form. They were also a product of mass production. The seventies, with the focus on individuality and consultation, saw the production of homes shift towards small-scale neighbourhoods with façades which made small groups of homes readable. The last two decades of the twentieth century were characterised by more sober façades and larger residential buildings. The façades project neutrality and the anonymity of living in the town or city. The diversity of the façades and the choice of material have increased dramatically and are also used to express the luxury of living in the city. The façade and the public (chapter 6) The gradual transition from street to house in the town or city in the Netherlands has been present for centuries. The border between the two was vague, people worked both in front of, and in the house. An important change for living in the town or city was the disappearance of city walls and gates after 1874 as a consequence of the vestigingswet [‘Settlement Act’], which allowed non-residents into the city or town without checks, and when the front door was established as the border between the public and the private. The façade became a necessary border between the public and the private. The street lost its importance as public space for those living on it as traffic increased. The introduction of the residential building only increased the distance to the street. The anonymization of the street also played a large role throughout the whole of the twentieth century. The functionalists rejected the street and wanted to connect homes with recreation and green spaces. Urban blocks of buildings were opened up as was the layout of residential buildings. This resulted in residential buildings which had several façades which were visible to the public. In the seventies, some architects, like Herman Hertzberger, returned the street to the resident and a pedestrian friendly zone in front of homes (the woonerf) was created. The house façades on the residential areas allowed openness and space to be seen, fusing the public and the private. This approach was quickly followed by a reintroduction of a distance to the street. The last two decades of the twentieth century were characterised by a withdrawal of the social filter role to behind the façade. The street’s role as part of the home can only be found in very protected environments. The façade and private living (chapter 7) Private living was initially led by an increasing embarrassment and hygiene. The need to retreat further into the house gave rise to a more differentiated layout even in the traditional house and this can be read from the façade. In the second half of the nineteenth century, the privacy of the home was lost when it was housed with several others in the one building and by the internal entrance in a relatively open landing on the upper floors. The first two decades of the twentieth century saw various entrances which made privacy possible such as the entrance stairwell and the gallery. The homes received their own front doors with a hall behind them. At subsistence level, privacy was reduced to a very small space and this would only change after the Second World War; regulations for minimum surface areas in the fifties contributed to this. Economic growth in the sixties and seventies allowed a need for individual development and private space within the family. Increasing preferences for homes resulted in a greater diversity but also in neutral houses which could be adapted. The façade reflects this. Privacy at the end of the twentieth century meant freedom of choice. The residential building showed the consideration for this freedom in a neutral façade. The case studies (chapter 8) The case studies reflect the various phases of the changes in the residential building and its façade. The ten projects chosen can be found in the Dutch town or city and have all been designed as homes. The projects chosen are: 1914 – The Hague portico Copernicuslaan, Den Haag, architect unknown 1911-15 – Dwellings in the Indische Buurt, Amsterdam, architect H.P. Berlage 1918-22 – Justus van Effen Complex, Rotterdam, architect M. Brinkman 1925–26 – Residential building Oldenhoeck, Amsterdam, architect P.A. Warners 1932–34 – Bergpolder Flat, Rotterdam, architect W. van Tijen 1955-58 – Dwellings Pendrecht IV, Rotterdam, architects J. en L. de Jonge 1962-68 – Dwellings Het Breed, Amsterdam, architect F. van Gool 1969–76 – Dwellings Molenvliet, Papendrecht, architect F. van der Werff 1978–82 – Dwellings Haarlemmer Houttuinen, Amsterdam, architect H. Hertzberger 1994–98 – City block De Landtong, Rotterdam, architect CIE, F. van Dongen The first two cases just have six to eight homes per staircase per floor and their entrances are richly decorated while the Justus van Effencomplex and, in the sixties, Het Breed project with a gallery bring many more homes together and their entrances are less expressively designed. At the end of the twentieth century, the Landtong connects the homes visually with each other by means of an internal corridor with a void allowing the other floors to be seen. The expression of the collective and the individual through the century is very different; the home cannot always be read from the façade. Conclusion The most important conclusion from this research is that the social filter between the public and the private today often lies behind the screens, so that the transition between the public space and the façade is less gradual and the expressiveness of the façade is different and achieved by other means. The façade is more of a mask to protect the anonymous home than a face that exhibits it. The line between a façade as a face or a mask is not always clear, however, because the perspective of the person looking at it can change. A façade can create an illusion in the distance, but show the home from close by. This study demonstrates the development of the residential building and its façade in the Netherlands with the focus on their development in the twentieth century. The relationship of the façade with the immediate public space surrounding the home and the relationship of the façade with the private home have been important starting points for this study. It places the façade as an important element in protecting the home and as well as an expression of it. The study demonstrates a way of looking at the façade which is very important for design decisions for new construction but also for maintenance and conservation.